EFEKTIVITAS TEKNIK SELF-MANAGEMENT DENGAN KONSELING KELOMPOK UNTUK MENURUNKAN PROKRASTINASI AKADEMIK SISWA SMP AL-ISLAM KRIAN - Dimas Ardika Miftah Farid; Sofiea Cameilya Putri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This research aims to determine the effectiveness of self-management techniques with group counseling to reduce the academic procrastination of Al-Islam Krian Middle School students. This research uses self-management techniques with group counseling. This research uses quantitative methods with a one group pre-test post-test design. This research only used one experimental class without using a control or comparison class. This experimental class is obtained from the results of a measurement scale that has been distributed to the population, after which it will be known which subjects will fill the experimental class. Based on the results of the discussion, there were 6 students who had high academic procrastination and this was seen from the results of the pre-test and post-test that had been given. The results of the Wilcoxson test performed showed that Asymp. Sig. (2-tailed) is worth 0.028. Because the value of 0.028 is smaller than 0.05, it can be concluded that the hypothesis is accepted. So that self-management techniques in group counseling are effective in reducing the academic procrastination of Al-Islam Krian Middle School students.